Practical View on Fund Based Accounting: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The outcome of financial transactions of fund based accounting in educational institutions may show different results depending upon accounting practices, methods and accounting standards followed by that unit. Therefore, there is need to device a uniform system of fund based accounting for educational institutions so that similar types of transactions do not result in different > financial results.The aim of the present study is to critically review the existing accounting practices of higher education institutions and to suggest better methods of classification and highlight the financial status. Efforts have been made to suggest a model which is legally compliant and draws from the best accounting practices. The model shall be applicable to all types of higher educational institutions and shall provide a uniform basis for comparison of financial results amongst various institutions.